Financial recovery schemes in Austria: how planned relocation is used as an answer to future flood events. (26th May 2020) - Thaler, Thomas; Fuchs, Sven
ABSTRACT: Damages due to extreme hydro-metrological events request for additional efforts to enhance the implementation of property level flood risk adaptation (PLFRA) measures. Although a highly effective long-term measure, the planned relocation of individuals from areas at risk is rarely considered as an adaptive response. We evaluate how financial recovery schemes are actually linked to planned relocation option in two study sites in Austria. In both areas, more than 500 households were offered a voluntary planned relocation directly after extreme flood events. We conducted a semi-structured qualitative approach with 16 key respondents in order to identify how current financial recovery schemes are linked to ongoing and past relocation processes. The results show that there exists a missing link between disaster-aid payments and compensation for planned relocation. Participants gained from the programmes and used disaster-aid compensation schemes to increase the economic value of their houses. In addition, the financial schemes were not used to encourage further sustainability transition processes at local level. These data demonstrate the uneven distribution of payments with strong socio-economic implications for those who take part in planned relocation process. We recommend a better link between financial disaster-aid compensation and voluntary payout programmes, especially to reduce the uneven socio-economic distribution during the recovery phase.